OPTIMALISASI PENERIMAAN SISWA DI SMAN 2 SERUWAY MENGGUNAKAN METODE DATA ENVELOPMENT ANALYSIS - Evi Ariani; Dahlan Abdullah; Cut Agusniar (LPPM Universitas Abdurrab, 2025)
This study aims to analyze the efficiency level of the student admission process at SMAN 2 Seruway, Aceh Tamiang Regency, using the Data Envelopment Analysis (DEA) method. DEA was chosen because it is able to evaluate the relative efficiency of decision-making units that have many inputs and outputs without assuming the form of a production function. This method is considered more flexible than other methods such as MOORA, which are deterministic. The inputs used include parents' occupations, school of origin, and student majors, while the outputs are the Final School Exam (UAS) scores for science and social studies subjects. Data were analyzed for three Decision-Making Units (DMUs): 2022, 2023, and 2024. The results showed that 2022 was inefficient (efficiency 0.93), while 2023 and 2024 experienced high efficiency (1.14 and 1.06). Values above 1 indicate super-efficiency, indicating superior resource utilization. The final science exam score consistently dominated efficiency, while social studies scores showed no contribution. Similarly, from an input perspective, student majors were the most influential factor, while parental occupation and school of origin tended to be less influential. This study is limited by its three-year data period and its failure to consider non-academic variables. Practical implications of this research include the need to strengthen science subjects and map appropriate majors within student admissions strategies. Furthermore, DEA results can be used as a policy basis for allocating school resources more efficiently